Perancangan Media Promosi Prima Boga Sebagai Upaya Meningkatkan Brand Awareness - Imansyah, Surya Adi; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The development of household appliances industry, especially the kitchen equipment in Indonesia can be said is not comparable with the development of the culinary industry very rapidly in Indonesia, which until now, according to the Ministry of Industry of the Republic of Indonesia, the food and beverage industry grew by 13% or approximately Rp. 390 Trillion per year (http://www.kemenperin.go.id:04/03/2016) One of the producers of cookware that has existed since 1998, Prima Boga made products, especially pan kitchen equipment that can be said the main component in cooking in some countries in southeast Asia such as Vietnam, China and Indonesia and markets its products in various cities in Indonesia, one of Surabaya. Although it has long stood as a manufacturer of kitchen appliances in Indonesia with an extensive distribution chain, the public is not fully aware of the existence and reputation of the company. Therefore, the purpose of this research is directed to design a media campaign Prima Boga an effort to increase brand awareness.Keywords: Media Promotion, Prima Boga, Brand Awareness, Illustration, Vector.